Studies On Haemorrhagic Septicaemia In Cattle And Buffaloes In Peninsular Malaysia - Saharee, Abdul Aziz (1992)

(untitled)
Haemorrhagic septicaemia is an acute septicaemic disease caused by Pasteurella multocida types 6:B and 6:E. It affects mainly cattle and buffaloes and is characterised by a rapid course, loud stertorous breathing, oedematous swelling and petechial haemorrhages in the throat and brisket region. The disease is responsible for acute deaths causing severe economic losses to the farmers. Haemorrhagic septicaemia has long been present in the country and many attempts have been made to understand and control the disease. Currently, despite prophylactic vaccination, outbreaks of the disease continued to be reported. A review of the literature on HS indicates that there are gaps in our understanding of the disease in Malaysia. A retrospective study using questionnaires sent to all District Veterinary Officers showed that the disease is endemic in the East Coast states of Peninsular Malaysia (Kelantan, Terengganu and Pahang). The disease was observed to occur at any time of the year, contrary to the long-held belief that HS occurs during the monsoon season. Although the incidence can be higher during rainy seasons, the time series studies showed that rain per se did not influence the frequency of the disease. Six major outbreaks were investigated in the states of Perak, Melaka, Negeri Sembilan, Johor, Terengganu and Kelantan. Field and experimental observations suggest that buffaloes are more susceptible than cattle to the disease.